IMPROVING AQUISITION OF BUSINESS VOCABULARY USING TABOO WORD GAME - Aizan Yaacob; Mathevan Narayanan; Ina Suryani; Patricia Michael; Yulianeta Yulianeta (Journal of Human Development and Communication (JoHDeC), 2025)
Methods of teaching vocabulary in an ESL context are highly debatable and implicit. Having for-mal lesson or solely focusing on providing meaning and examples are among the conundrums that language educators must face. Thus, language game is commendable as it allows the students to practice or utilize the knowledge that they acquired in a non-traditional and interesting way. This study explores the effectiveness of Taboo Word Game (TWG) in improving business vocabulary of 23 private college students in one of the private colleges in Malaysia. It also explored students’ experiences in using TWG in learning business vocabulary and reports on the pre-post-tests results. Comparison of mean scores on both pre and post-tests was done are reported. The findings revealed that TWG helped to improve students’ vocabulary competency. The implication on vocabulary teaching is that even at the college level, games should be incorporated to boost students learning needs and preferences.